Pediatric neurosurgery AC-after COVID-19: What has really changed? A review of the literature - Noris, Alice; Peraio, Simone; Di Rita, Andrea; Ricci, Zaccaria; Spezzani, Chiara; Lenge, Matteo; Giordano, Flavio (Frontiers in Pediatrics, 2022)
The COVID-19 outbreak has dramatically changed the organization of Pediatric Neurosurgery all over the world. The departments involved developed similar plans to maintain emergency surgeries without reducing clinical activities. The Association of Pediatric Neurosurgeons wrote different memoranda to detail the surgical procedures not to be postponed with special attention given to high-risk pathology for COVID-19 contamination, like trans-naso-sphenoidal surgery. On this basis, we have conducted a complete literature review focusing on many topics: hospital organization, patients and parents screening, surgical indication criteria, outpatient clinic and teleconsultation, telematic conference and meeting, fellowship and training, and virtual multidisciplinary meeting.